2018
DOI: 10.1159/000486751
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of the Immature Infant: A Commentary and Recommendations for Oxygen Saturation Targets and Alarm Limits

Abstract: Background: For 70 years, there has been a search for the optimal oxygenation of premature infants. In spite of the lack of evidence, guidelines have successively reduced oxygenation targets during these years. Objectives: (1) To present a summary of previously published meta-analyses of 5 randomized studies (NeOProM) which tested a low (85–89%) versus a high (91–95%) oxygen saturation target the first weeks after birth on outcome of immature newborn infants. (2) To present international recommendations for ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…An animal study suggested that chronic exposure to FiO 2 > 85% results BPD phenotype 19. Forty percent of our respondents chose FiO 2 > 40% as part of their decisions for intubation, which suggests the cautious approach against using high concentration of oxygen 23. This is consistent with the recent updated European consensus guideline, which…”
supporting
confidence: 87%
“…An animal study suggested that chronic exposure to FiO 2 > 85% results BPD phenotype 19. Forty percent of our respondents chose FiO 2 > 40% as part of their decisions for intubation, which suggests the cautious approach against using high concentration of oxygen 23. This is consistent with the recent updated European consensus guideline, which…”
supporting
confidence: 87%
“…Targeting lower saturations (85–89 vs. 91–95%) reduces risk of severe retinopathy of prematurity (ROP) but at expense of increasing mortality (relative risk [RR] 1.17; 95% confidence interval [CI] 1.04–1.31) and NEC. Recommendations have therefore remained the same, targeting saturations between 90 and 94% by setting alarm limits between 89 and 95% although it is acknowledged that ideal oxygen saturation targets are still unknown [84]. Episodes of intermittent hypoxaemia and bradycardia are associated with increased risk of late death or disability at 18 months, and these should be avoided if possible [85].…”
Section: Oxygen Supplementation Beyond Stabilisationmentioning
confidence: 99%
“…In clinical practice, successful weaning of O 2 IT in infants with CLD is determined not only by the infant's ability to maintain oxygen saturations in an “acceptable” range for a “sufficient” period of time, but also by the ability to feed and demonstrate optimal growth. Furthermore, there is great variability in the SpO 2 values considered “acceptable” in US NICUs [ 48 , 49 ]. The period of time that an infant is monitored after discontinuing oxygen is similarly variable.…”
Section: Discussionmentioning
confidence: 99%